Solve the 2-step equation for x: -4x+8 = 16
1. First, you will combine the like terms. The like terms we have here are 8 and 16. We will subtract 8 from both sides, giving us -4x = 8. 2. Now you will divide both sides by -4 in order to isolate the x. After we divide both sides by -4, this gives us an answer of x = -2.
What is 5-3?
Let's say you have 5 cookies, and then you eat 3 of the cookies. When you eat 3 of the cookies, you are taking 3 of them away, which will leave you with 2 cookies. So our answer to 5-3 is 2.
Solve for x: 6(x+1) = 3(x-1)
1. First, you will use the distributive property on both sides of the expression. You will distribute the 6 to the x and the 1 on the left side, and then you will distribute the 3 to the x and the -1 on the right side. You will then have 6x+6 = 3x-3. 2. Next, you will combine like terms. The like terms we have are 6x and 3x, and 6 and -3. We will subtract 3x from both sides to get 3x+6 = -3. Then we will subtract 6 from both sides to get 3x = -9. 3. The last step is to divide each side by 3 so we can isolate the variable, x. This gives us the answer of x = -3.